Impact of daily soft‐tissue image guidance to prostate on pelvic lymph node (PLN) irradiation for prostate patients receiving SBRT. Issue 7 (17th June 2019) - Tyagi, Neelam; Hipp, Elizabeth; Cloutier, Michelle; Charas, Tomer; Fontenla, Sandra; Mechalakos, James; Hunt, Margie; Zelefsky, Michael
Abstract: Purpose: To determine the impact of using fiducial match for daily image‐guidance on pelvic lymph node (PLN) coverage for prostate cancer patients receiving stereotactic body radiation therapy (SBRT). Methods: Thirty patients underwent SBRT treatment to the prostate and PLN from 2014 to 2016. Each patient received either 800cGy × 5 or 500cGy × 5 to the prostate and 500cGy × 5 to the PLN. A 5 mm clinical target volume (CTV)‐to‐planning target volume (PTV) margin around the PLN was used for planning. Two registrations with planning computed tomography (PCT) for each of the daily cone beam CTs (CBCTs) were performed: a rigid registration to fiducials and to the bony anatomy. The average translational difference between fiducial and bony match as well as percentage of fractions with differences > 5mm were calculated. Changes in bladder and rectal volume as well as center‐of‐mass (COM) position from simulation parameters, and their correlation with translational difference were also evaluated. The dosimetric impact of the translational differences was calculated by shifting the plan isocenter. Results: The average translational difference between fiducial and bony match was 0.06 ± 0.82, 2.1 ± 4.1, −2.8 ± 4.3, and 5.5 ± 4.2 mm for lateral, vertical, longitudinal, and vector directions. The average change in bladder and rectal volume from simulation was −67.2 ± 163.04 cc (−12 ± 52%) and −1.6 ± 18.75 (−2 ± 30%) cc. The average change in COM of bladder from the simulation position was 0.34 ± 2.49, 4.4 ± 8.1, and −3.9 ± 7.5 mm along the LR, AP, and SI directions. The corresponding COM change for the rectum was 0.17 ± 1.9, 1.34 ± 3.5, and −0.6 ± 5.2 mm. Conclusions: The 5 mm margin covered ~75% of fractions receiving PLN irradiation with SBRT, daily CBCT and fiducial‐guided setup. The dosimetric impact on PLN coverage was significant in 19% of fractions or 25% of patients. A larger translational shift was due to variation in rectal volume and changes in COM position of the bladder and rectum. A consistent bladder positioning and/or rectum filling compared with presimulation volume were essential for adequate coverage of PLN in a hypofractionated treatment regime.